(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Bean pod borer, Maruca vitrata Geyer is a key pest of bean causing up to 80 percent yield loss. The present study was conducted at the Entomology Field Laboratory of Bangladesh Agricultural University, Mymensingh, Bangladesh during October 2017 to March 2018 to evaluate the bioefficacy of some novel insecticides and biopesticides for managing bean pod borer on BARI Shim-2. Treatments were evaluated based on different parameters viz. no of healthy and infested pod, percent pod infestation, and marketable pod yield (t/ha). The experiment was laid out in RCBD with 3 replications of each treatment. Eight treatments viz. T1: Cartap (Suntap 50 SP), T2: Flubendiamide, (Belt 24 WG), T3: Lufenuron (Heron 5EC), T4: B. bassiana, T5: Cypermethrin, T6: Spinosad (Libsen 45Sc), T7: Emamectin benzoate (Suspend 5SG) and T8: Untreated control. Treatments were applied at seven days interval and data were also collected seven days of each spraying. All the treatments significantly reduced bean pod borer infestation in the field. The best result was found in case of Emamectin benzoate treated plots which showed the highest cumulative mean number of healthy pod (46.00) and the highest increase of healthy pod (63.29%) over control by number, the lowest cumulative mean number of infested pod plot-1 (2.88) and the highest reduction of infested pod over control (69.215%) by number. The highest cumulative mean weight of healthy pods plot-1 (240.66g), the highest percent increase of healthy pod over control (34.03%) by weight, the lowest cumulative mean weight of infested pods plot-1 (6.44g) and the highest (%) reduction of infested pod weight over control (65.02%) were also obtained from Emamectin treated plots. Among the treatments the highest yield (7.1 ton ha-1) and yield increase over control (32.58%) were also found from Emamectin. Cartap (Suntap 50 SP) showed the second best performance regarding the above parameters including the second highest yield (6.4 ton ha-1). The lowest performance was always obtained from untreated control in case of all parameters studied. Though Cartap was very effective but considering the environmental issue Emamectin benzoate (Suspend 5 SG) would be recommended for sustainable management of bean pod borer in the field. J Bangladesh Agril Univ 18(2): 221–226, 2020 https://doi.org/10.5455/JBAU.96967